The curriculum of Islamic studies and Islamic studies education programmes in meeting the challenges of globalization: a case study of selected Malaysian Universities - Hashim, Rosnani (2014)
Islamic studies or religious instruction is a subject that is continuously taught throughout primary and secondary schooling, a period of about twelve years to Muslim students. This testifies its importance in either for preservation of the Islamic tradition on the one hand, and the precursor of change within the Muslim mind and soul, on the other. This subject provides a great opportunity to transform Muslims especially in the era of globalization that is filled with challenges including the spread of Islamophobia. The paper argues that the transformation is only possible if the curriculum of Islamic studies and Islamic studies education programmes which produce the teachers of Islamic studies are sound and considers the contemporary situations. Two important elements in rising to the challenge of globalization and in line with the aims of higher Islamic studies is intellectualism and relevance of the Programmes. Hence, this paper examines the curriculum of higher Islamic Studies programme in three universities and that of an Islamic Study teacher preparation programme in Malaysia for their adequacy in generating Islamic intellectualism and relevance in the context of globalization. The study found that the Islamic Studies Programmes are still traditional in general, although some changes have been taken to be relevant. But it still lacks the ingredient of intellectualism due to its pedagogy. The paper proposes some changes in the curriculum for its improvement.